THE ANALYSIS OF MORAL VALUES IN DANGEROUS MINDS MOVIE BY JOHN N. SMITH - Anisa Alawiyyah; Sri Hastin Oktavi (Department of English Education, Universitas Panca Sakti Bekasi, 2019)
This research aims is to find out: The intrinsic element in Dangerous Minds Movie by John N. Smith, The kinds of moral values in Dangerous Movie Minds by John N. Smith, The Cause of the moral value in Dangerous Minds Movie by John N. Smith, The solution of moral values in Dangerous Minds Movie by John N. Smith. The research method used is content analysis and literary psychoanalysis. The subject of the study was Dangerous Movie Minds by John N. Smith. The results of this study include the intrinsic elements in Dangerous Movie Minds by John N. Smith are theme, plot, characterization and background. The kinds of moral values found in this research are honesty, authentic value, self-confidence, moral independence, humility, responsibility, tenacity, reality and crisis, moral faith and courage. These findings suggest that this technique is effective for analyzing the moral values in Dangerous Minds Movie by John N. Smith.